Fish tracks and hydrodynamics at the navigation lock complex in Kwaadmechelen (Albert Canal, Belgium) - Vergeynst, Jenna (Zenodo, 2019)
Description Swimming tracks of European silver eels (Anguilla anguilla) upstream of the navigation lock complex in Kwaadmechelen (Albert Canal, Belgium), calculated with the YAPS algorithm. The swimming direction of the tracks is from square to circle. The eels were tagged with V9 and V13 Vemco transmitters, with a random burst interval of 17-33 seconds. The flow at the upstream side of the complex is modelled by use of CFD (Computational Fluid Dynamics) for one of the following events occurring during the fish track: filling of the Northern Lock (NL), filling of the Middle Lock (ML), filling of the Pushed Convoy Lock (PCL) and operation of the hydropower turbines. The left panel of each figure contains time series of parameters characterising the track, from top to bottom: fish-flow angle (angle), water velocity at the fish position (U), water acceleration at the fish position (A), distance to flow source (dist), discharge of the lock filling (flow), progress of the filling in minutes (min), fish velocity (V fish) and turning angle (turn). Files Kwaadmechelen_study_area.jpg : air picture of the navigation lock complex, with the different structures indicated lock_filling_passage_LOCK_ID_x.png : track during filling of a lock, followed by passage of the lock lock_filling_nopassage_LOCK_ID_x.png : track during filling of a lock, but not followed by passage of the lock no_flow _ID_x.png : tracks during periods when no flow is present turbine_flow_passage_xcub_ID_x.png : track during turbine operation (at ... m3/s) followed by passage via one of the turbines turbine_flow_nopassage_xcub_ID_x.png : track during turbine operation (at ... m3/s) not followed by passage via one of the turbines : This work makes use of data and/or infrastructure provided by VLIZ and INBO and funded by Research Foundation - Flanders (FWO) as part of the Belgian contribution to LifeWatch.